To Live but Die Inside: A Lamentable State of Montressor in â€œThe Cask of Amontilladoâ€ - C. Francisco, Jesusa (OKARA: Jurnal Bahasa dan Sastra, 2021)
The enduring quality of "The Cask of Amontillado" makes it a timeless classic in which researchers from different generations offer a variety of subjective interpretations. This study aims to look closer to the story of "The Cask of Amontillado" to reveal other underlying themes. The themes were identified using content/textual analysis and a humanistic literary approach in interpreting meanings. The themes discovered involve excessive self-esteem, a penchant for prestige, lusting for another’s good fortune (envy), and love deprivation. These themes, in a way, express the psychological needs of humans reflected in Maslow’s Hierarchy of Needs. Left unsatisfied, these basic human needs (self-esteem, prestige, and love) led to the characters’ downfall because their thoughts and actions were inconsistent with ethical conduct. Findings of the study may add to the existing interpretations of the story, which primarily discuss and look into the various facets of its overarching theme of revenge along with Montressorâ€™s mental condition.